Juridical Review of Trademark Disputes in Indonesia: Case Study Ruling No. 92 K/PDT.SUS-HKI/2017 Trademarks between HUGO BOSS And HUGO - F Fatmawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
Most people in Indonesia pay relatively high nominal prices for well-known brands. Situations like this provide an opportunity for unscrupulous businesses to approve the use of a recognizable brand. It is very detrimental for the original owners of well-known foreign brands to infringe their IPRs and thereby reduce their income from the sale of goods or services. Owners must register their trademarks to protect them legally. The problems in this research will be discussed using doctrinal method analysis. The purpose of this research is to determine the position of the owner of the Hugo Boss and Hugo trademarks in terms of Indonesian law and to determine the legal consequences following the Commercial Court decision no. 92 K/PDT.SUS-HKI/2017. Hugo's position is in accordance with Article 21 Paragraphs 1, 2 and 3 of Law Number 20 of 2016 concerning Marks and Geographical Indications. The legal consequences include granting the cassation petition submitted by the cassation plaintiff, HUGO BOSS TRADE MARK MANAGEMENT GMBH & CO. the KGs, and cancel the decision of the Commercial Court at the Central Jakarta District Court Number 30/Pdt.Sus.Merek/2016/PN Niaga on October 3 2016, in Jakarta PST.